Hep‐CORE: a cross‐sectional study of the viral hepatitis policy environment reported by patient groups in 25 European countries in 2016 and 2017. (10th April 2018) - Lazarus, Jeffrey V; Stumo, Samya R; Harris, Magdalena; Hendrickx, Greet; Hetherington, Kristina L; Maticic, Mojca; Jauffret‐Roustide, Marie; Tallada, Joan; Simojoki, Kaarlo; Reic, Tatjana; Safreed‐Harmon, Kelly; ,
Abstract: Introduction: The first World Health Organization (WHO) global health sector strategy on hepatitis B and C viruses (HBV and HCV) has called for the elimination of viral hepatitis as a major public health threat by 2030. This study assesses policies and programmes in support of elimination efforts as reported by patient groups in Europe. Methods: In 2016 and 2017, hepatitis patient groups in 25 European countries participated in a cross‐sectional survey about their countries' policy responses to HBV and HCV. The English‐language survey addressed overall national response; public awareness/engagement; disease monitoring; prevention; testing/diagnosis; clinical assessment; and treatment. We performed a descriptive analysis of data and compared 2016 and 2017 findings. Results: In 2017, 72% and 52% of the 25 European study countries were reported to not have national HBV and HCV strategies respectively. The number of respondents indicating that their governments collaborated with civil society on viral hepatitis control increased from 13 in 2016 to 18 in 2017. In both 2016 and 2017, patient groups reported that 9 countries (36%) have disease registers for HBV and 11 (44%) have disease registers for HCV. The number of countries reported to have needle and syringe exchange programmes available in all parts of the country dropped from 10 (40%) in 2016 to 8 in 2017 (32%). In both 2016 and 2017, patient groups in 5 countries (20%) reported that HCV treatment is available in non‐hospital settings. From 2016 to 2017, the reported number of countries with no restrictions on access to direct‐acting antivirals for HCV increased from 3 (12%) to 7 (28%), and 5 fewer countries were reported to refuse treatment to people who are currently injecting drugs. Conclusions: The patient‐led Hep‐CORE study offers a unique perspective on the readiness of study countries to undertake comprehensive viral hepatitis elimination efforts. Viral hepatitis monitoring should be expanded to address policy issues more comprehensively and to incorporate civil society perspectives, as is the case with global HIV monitoring. Policy components should also be explicitly added to the WHO framework for monitoring country‐level progress against viral hepatitis.